PERAN INSPEKTORAT DAERAH KABUPATEN KEBUMEN DALAM PELAKSANAAN SISTEM PENGENDALIAN INTERN PEMERINTAH PADA PEMERINTAH DAERAH KABUPATEN KEBUMEN - Rokhyatun , Eti; Setyawati, Rufaida; Zulkifli, Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The Internal Control System as stipulated in Government Regulation No. 60 of 2008 concerning SPIP is defined as “an integral process within continuous actions and activities carried out by leaders and all employees to provide reasonable assurance regarding the achievement of organizational objectives through effective and efficient operations, reliable financial reporting, safeguarding of state assets, and compliance with laws and regulations.” The regulation further states that the Regency/Municipal Inspectorate serves as the Government Internal Supervisory Apparatus directly responsible to the Regent/Mayor. This study aims to examine the role of the Kebumen Regency Inspectorate in implementing the Government Internal Control System (SPIP) within the Kebumen Regency Government and to identify obstacles that affect its role in SPIP implementation. The data used in this research consist of primary data obtained through interviews with key informants and secondary data derived from documentation and reports. A qualitative data analysis method was employed. The findings indicate that the Kebumen Regency Inspectorate functions as the coordinator of SPIP implementation and serves as the third line of defense, carrying out internal audits, other supervisory activities, governance risk control, and consulting. The study also reveals several obstacles that hinder the Inspectorate’s role in SPIP implementation, including limited human resources, budget constraints, insufficient examiner competence, the broad scope of audit objects in Kebumen Regency, low risk awareness among employees at all organizational levels, and a lack of understanding among regional government units regarding the importance of SPIP.